A Hybrid Multi-Criteria-Decision-Making Method and Geographic Information System for Selecting the Location of Wood Production Factories Using Palm Wastem - Mansouri, Elahe; Kashan, Ali Husseinzadeh; Dahooie, Jalil Heidary; Zavadskas, Edmundas Kazimieras (Transformations In Business & Economics, 2025)
In recent years, the shortage of forest resources and the increase in demand for wooden products have faced severe challenges in the wood and paper industry. According to the surveys conducted, the branches and waste from palm pruning can be used for conversion industries, including the production of chipboard and medium-density fiberboard (MDF). The surface of Iran has significant coverage of palm trees, and currently, a large amount of waste from these trees is thrown away and burned. Therefore, the topic chosen in this research is to determine the location for building the wooden products production factory, aiming at optimal use of palm waste and helping to compensate for the lack of wooden production in the country. First of all, suitable criteria for building a wooden products factory are determined through sources and experts“ opinions. Then, they are prioritised and weighted using a questionnaire based on the BWM method. In the next step, ArcGIS software is used to apply the criteria on the level under investigation. Decision options are ranked using TOPSIS, ARAS, COPRAS, WASPAS, MULTIMOORA, VIKOR, SAW and CODAS decision-making methods. Then the obtained results are collected using the CRITIC method, and the best construction places are determined. When different decision-making methods are combined, the accuracy and strength of the obtained results also increase.
Keywords: location facility; multi-criteria decision-making; geographic information system; MCDM; Aggregation method